2009
DOI: 10.1203/pdr.0b013e3181975ee4
|View full text |Cite
|
Sign up to set email alerts
|

New Potential Adjuncts to Treatment of Children With Type 1 Diabetes Mellitus

Abstract: Insulin administration is the primary therapy for type 1 diabetes mellitus (T1DM). Current available insulin therapies do not successfully enable children with T1DM to reach glycemic goals without side effects such as hypoglycemia and weight gain. Pramlintide is a synthetic analog of human amylin that acts in conjunction with insulin to delay gastric emptying and inhibit the release of glucagon and is indicated for use in patients with type 1 and type 2 diabetes. Recent studies in adult patients have examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
(59 reference statements)
0
8
0
3
Order By: Relevance
“…Die generell niedrige Exenatid-Dosis wurde aufgrund des pädiatrischen Klientels gewählt. Bei einem Teilnehmer trat eine anhaltende Hypoglykämie auf [9].…”
Section: Methodik ▼unclassified
See 2 more Smart Citations
“…Die generell niedrige Exenatid-Dosis wurde aufgrund des pädiatrischen Klientels gewählt. Bei einem Teilnehmer trat eine anhaltende Hypoglykämie auf [9].…”
Section: Methodik ▼unclassified
“…Sie zeigen alle einen vielversprechenden therapeutischen Effekt von GLP-1-Analoga bei Typ-1-Diabetes [2,3,6,9,12], jedoch wird die methodische Beurteilung der eingeschlossenen Literatur nicht näher beschrieben. Auch sind in nur drei der fünf Reviews die Ein-und Ausschlusskriterien definiert, so dass die Ergebnisse insgesamt kritisch zu betrachten sind [2,3,12].…”
Section: Methodik ▼unclassified
See 1 more Smart Citation
“…Despite the goal of withdrawing insulin therapy after its initial introduction, only 28% of patients were able to come off insulin, and of those, 60% required reinitiation of insulin because of poor control (28). It should be noted that the use of insulin for optimal blood glucose control is accompanied by excessive weight gain and the risk of hypoglycemia (32). Adherence rates to multiple daily injections of insulin have been lower than other hypoglycemic agents in studies involving adults and children (33), and, thus, while insulin can be effective, its drawbacks necessitate consideration of alternative or adjunctive therapy options.…”
Section: Treatment Of Youth With Type 2 Diabetesmentioning
confidence: 99%
“…First preclinical studies suggest that theoretically such a combination therapy may be feasible in the future [106]. Besides the positive effect on the beta cells, GLP-1 may also influence glycaemic parameters in a favourable way by slowing gastric emptying and affecting glucagon secretion in type 1 diabetes [107]. A small mechanistic study in type 1 diabetic individuals showed that an intravenous GLP-1 infusion reduced fasting hyperglycemia in the morning, which was provoked by omitting the basal insulin injection at night [108].…”
Section: Incretin-based Therapies and Type 1 Diabetesmentioning
confidence: 99%